Faktor-Faktor yang Mempengaruhi Indeks Pembangunan Gender (IPG) Provinsi Sumatera Barat Menggunakan Analisis Regresi Data Panel - Ira Elisa; Helma Helma (UNIVERSITAS NEGERI PADANG, 2022)
Gender differences are closely related to human development. Where gender is not the main determinant to achieve gender equality in human development which is the main focus in this regard. An index that is used to measure human success in seeing disparities that occur based on gender is often referred to as the Gender Development Index (GDI). The important objective of this research is to form a model that best describes the factors that have the most significant influence on the Gender Development Index (GDI) of West Sumatra Province in 2017-2020 with panel data regression analysis. At the significance level of 5% the factors that have a significant effect are the average length of schooling and at the significance level of 15% the factors that have a significant effect are the expectation of school years and the level of labor force participation rate.